Profil Penggunaan Obat dan Suplementasi pada Pasien Thalasemia di Rumah Sakit Daerah: Implikasi terhadap Kebijakan Pelayanan Kesehatan Nasional - dewy basuki; Yogi Bhakti Marhenta; Pri Hardini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Thalassemia is a chronic genetic disorder requiring lifelong management, including regular blood transfusions, iron chelation therapy, and supportive supplementation. Regional hospitals play a strategic role in providing thalassemia care; however, data on drug and supplement utilization at the regional level remain limited. This study aimed to describe the profile of drug and supplement use among thalassemia patients in regional hospitals and to analyze its implications for national health service policies. This study employed a descriptive observational design with a retrospective approach. Data were collected from medical records of thalassemia patients treated at RSUD Ngudi Waluyo Wlingi, Blitar Regency, and RSUD Jombang, East Java. Variables observed included patient characteristics, transfusion therapy, iron chelation drugs, and supportive supplementation. Data were analyzed descriptively. The results showed that most patients with thalassemia major received regular blood transfusions and iron chelation therapy. Deferiprone was the most commonly used iron chelator, while folic acid was the main supportive supplement. Variations in additional supplementation, such as vitamin E and vitamin D, were observed between hospitals. Overall, treatment patterns were generally consistent with national guidelines, although variations in clinical practice were identified. The profile of drug and supplement use among thalassemia patients in regional hospitals generally aligns with national guidelines; however, variations in practice remain. These findings provide important evidence to support evaluation and strengthening of national health service policies to improve the quality and equity of thalassemia care in Indonesia.